An Analysis of Compliment Responses by Kuwaiti EFL Learners: A Pragmatic Approach - Alotaibi, Abdullah M. (European Scientific Journal, ESJ, 2016)
This study investigates the extent to which 80 female Kuwaiti EFL learners produce target-like compliment responses when they are communicating in English, through comparing their responses to those of British English speakers. It also examines whether the English proficiency level of Kuwaiti EFL learners plays a role in their responses to compliments in English. Essentially, this study explores whether pragmatic transfer has an impact on the Kuwaiti participants' responses. A Discourse Completion Task (DCT) was given to 50 female native speakers of British English (the control group) and to 80 female Kuwaiti EFL learners (the treatment group), in order to determine whether the responses of the latter group are similar or different to those of the former group. The results reveal that the English proficiency level of the treatment group had no effect on their answers on the DCT. In comparison with the control group, the results also demonstrate that the treatment group transferred both L1 expressions and strategies to respond to compliments in English. This has been attributed to the fact that they may not be aware of any culture-specific nature of verbal communications crosslinguistically, among other reasons. Finally, the study concludes with recommendations for further research.